COMPARISON OF INTENSIVE AND NON-INTENSIVE ENGLISH COURSES AND THEIR EFFECTS ON THE STUDENT’S PERFORMANCE IN AN EFL UNIVERSITY CONTEXT - E., Nasiri; N., Shokrpour (European Scientific Journal, ESJ, 2012)
The aim of this study was to assess the students’ performance in the intensive and nonintensive English courses in an EFL university context. More specifically, it aimed at determining whether the students attending the intensive course had a better gain than those in non- intensive one or not. To achieve the goal, 170 freshmen students at the international branch of Shiraz University of Medical Sciences were given a pre-test. Based on the results, they were divided into two groups. The cut off point for the division was considered 40 out of 100. Those falling below the cut-off point participated in the intensive course to be taught a pre-reading course as well as the required reading course, attending 10 hours a week. The ones above the cut-off point, however, participated in the non-intensive course, being held 4 hours a week. The same book, improving reading skills was thought in both classes. The course lasted 68 hours for non-intensive and twice as much for the intensive course. The achievement test at the end of the course was considered as the post-test. In order to analyze the data, Paired t-test was administered on the data. The results, in spite of what was expected, did not reveal a significant difference, i.e. the intensive course did not lead to the students’ outperformance, and neither did it compensate their weakness. Therefore, this paves the way for more research taking factors such as the students’ attitude about intensive courses into consideration.